Discriminatory fees, coordination and investment in shared ATM networks - Stijn Ferrari (National Bank of Belgium, 2010)
This paper empirically examines the effects of discriminatory fees on ATM investment and welfare, and considers the role of coordination in ATM investment between banks. Our main findings are that foreign fees tend to reduce ATM availability and (consumer) welfare, whereas surcharges positively affect ATM availability and the different welfare components when the consumers' price elasticity is not too large. Second, an organization of the ATM market that contains some degree of coordination between the banks may be desirable from a welfare perspective. Finally, ATM availability is always higher when a social planner decides on discriminatory fees and ATM investment to maximize total welfare. This implies that there is underinvestment in ATMs, even in the presence of discriminatory fees
Keywords: G21; L10; L50; L89; 330; investment; coordination; ATMs; network industries; empirical entry models; spatial discrete choice demand models; Electronic Banking; Bankentgelt; Konsumentenverhalten; Preiselastizität; Wohlfahrtsanalyse; Theorie; Belgien